Resting-State Functional Correlates of Social Cognition in Multiple Sclerosis: An Explorative Study - Bisecco, Alvino; Altieri, Manuela; Santangelo, Gabriella; Di Nardo, Federica; Docimo, Renato; Caiazzo, Giuseppina; Capuano, Rocco; Pappacena, Simona; d’Ambrosio, Alessandro; Bonavita, Simona; Trojsi, Francesca; Cirillo, Mario; et al. (Frontiers in Behavioral Neuroscience, 2020)
Theory of mind (ToM) is the ability to understand and interpret another person's beliefs, intentions (cognitive ToM) and emotions (affective ToM). ToM abilities have been showed to be impaired in patients with Multiple Sclerosis (MS) and have been related to structural brain damage, such as global and focal gray matter atrophy, and microstructural white matter damage. Although some studies have investigated the association between ToM abilities and task-based functional MRI, no studies to date have explored brain resting-state functional connectivity (RS-FC) abnormalities related to cognitive and affective ToM abilities in MS. The aim of this explorative study was to assess the contribution of RS-FC abnormalities of major brain network to ToM in MS patients. Forty-one non-depressed and cognitively preserved relapsing remitting (RR) MS patients (mean disease duration = 8.8±8.2 years; median Expanded Disability Status Scale= 1.5, range 0-6.5) and 25 sex, age and education-matched healthy controls (HC) underwent a neurological and neuropsychological examination and their cognitive (the ToM Pictures Sequencing Task, TMPS) and affective (the Reading the Mind in the Eyes Task, RMET) ToM was evaluated. All subjects underwent a 3T magnetic resonance imaging (MRI) protocol including structural and RS-fMRI (RS-fMRI) sequences. FC of the default mode (DMN), right and left fronto-parietal (FPN), executive (EN), salience (SLN), cerebellar (CN) and limbic (LN) networks was evaluated by independent component analysis. Regional gray matter atrophy was also assessed. MS patients performed worse in cognitive ToM tasks compared to HC. In MS group we found correlations between: 1) for DMN RSN: right middle temporal gyrus FC and reciprocity subscale of TMPS score; posterior cingulate cortex FC and first-order false-belief subscale of TMPS score; 2) for EN RSN: cingulate gyrus FC and total as well as reciprocity subscale of TMPS scores; 3) for LN RSN: right superior temporal gyrus and reciprocity subscale of TMPS scores. All detected RS-FC changes did not co-localize with regional gray matter atrophy. The results suggest that ToM in MS is associated with RS-FC changes of DMN, EN and LN. Further research with longitudinal studies is warranted to clarify the adaptive or maladaptive role of these FC abnormalities in MS.